Construction and analysis of a diabetic nephropathy related protein-protein interaction network reveals nine critical and functionally associated genes. (December 2019) - Jiang, Wenhao; Zhang, Zheng; Sun, Yan; Zhang, Yajuan; Zhang, Luyu; Liu, Handeng; Peng, Rui
Graphical abstract: Highlights: A diabetic nephropathy related protein-protein interaction network was constructed. Transcript-level differential expression doesn't correlate with centrality parameters. Nine proteins are not only central, but also located in one network module. Abstract: Diabetic nephropathy (DN) is one of the common diabetic complications, but the mechanisms are still largely unknown. In this study, we constructed a DN related protein-protein interaction network (DNPPIN) on the basis of RNA-seq analysis of renal cortices of DN and normal mice, and the STRING database. We analyzed DNPPIN in detail revealing nine critical proteins which are central in DNPPIN, and contained in one network module which is functionally enriched in ribosome, nucleic acid binding and metabolic process. Overall, this study identified nine critical and functionally associated protein-coding genes concerning DN. These genes could be a starting point of future research towards the goal of elucidating the mechanisms of DN pathogenesis and progression.